Surgical fixation of ulnar coronoid process fractures via mesh plate: A case report. (June 2022) - Makihara, Koichiro; Takeda, Shinsuke; Mitsuya, So; Yamauchi, Ken-ichi
Abstract: Introduction: The coronoid process of the ulna is the primary stabilizer of the elbow joint. There has not yet been an accurate off-the-shelf dedicated implant because fragments of coronoid process fractures are often small and diverse. The variable angle locking compression mesh plate 2.4/2.7 (Depuy Synthes, West Chester, PA, USA) acts as a versatile, low-profile implant that can be cut to suit the specific fracture pattern and fits anatomically. Case presentations: We report two cases of Regan–Morrey type II ulnar coronoid process fractures in terrible triad elbow injuries. In both cases, persistent instability was fluoroscopically diagnosed after repair of the lateral structures. We performed osteosynthesis for the ulnar coronoid process fractures using a mesh plate, which we cut into a rhombus-like shape and used as a buttress plate. Here we report the good results obtained thereof. Conclusion: Considering our positive experience with using mesh plates, the mesh plate may be a good method of fixation for ulnar coronoid process fractures.